The Effect of the Technology-Based Problem-Based Learning (PBL) Model on the Learning Outcomes of Fiqh Subject - Nasution, Rodiah; Isroqunnajah, Isroqunnajah; Gafur, Abd. (DIMAR: Jurnal Pendidikan Islam, 2024)
Technology integration in education has become crucial in enhancing student engagement and learning outcomes, especially in Islamic studies such as Fiqh. Conventional teaching methods often fail to engage students, effectively leading to suboptimal learning achievements. This study addresses the issue by investigating the impact of a Nearpod-based Problem-Based Learning (PBL) model on students' performance in Fiqh lessons, specifically at MTs Al-Ma'arif Badung Bali. The research fills a gap in the application of interactive technology-integrated pedagogies within Islamic education, aiming to improve understanding and motivation. The study employed a Non-Equivalent Pretest-Posttest Control Group Design using a quantitative experimental approach. Sixty-three students participated and were divided into experimental and control groups through purposive sampling. Data collection involved tests, interviews, and documentation, analyzed using t-tests following normality and homogeneity testing. Key findings reveal a significant improvement in learning outcomes post-intervention. The experimental group taught using the Nearpod-based PBL model, achieved an average score of 73.44 compared to 61.41 in the pre-intervention phase. The significance value of 0.000 indicates a notable positive effect of the intervention. These results suggest that incorporating interactive technology and problem-based approaches enhances student engagement, critical thinking, and understanding of Fiqh concepts. This study underscores the potential of innovative teaching methods in transforming Islamic education. By leveraging technology, educators can bridge the gap between traditional practices and modern educational demands, fostering a more interactive and practical learning environment. The findings contribute to the growing discourse on integrating digital tools into pedagogical practices and highlight the need for broader implementation in diverse educational contexts.